Analisis Implementasi Digitalisasi Layanan Administrasi Kepegawaian Pada Rumah Sakit Otak DR Drs M Hatta Bukittinggi - Kristina .; Almasdi . (CV. ITTC INDONESIA, 2025)
The rapid advancement of technology has led to the near-total replacement of manual systems with electronic ones. The Ministry of Health, as a governmental body overseeing the health sector, has undertaken various innovations to support programs aimed at improving the health status of the Indonesian population. This transformation extends beyond healthcare services to encompass internal organizational aspects, including the adoption of technology to enhance efficiency, transparency, and accountability. One such initiative is the implementation of the e-Office application, designed to digitize personnel administration with the goal of achieving more effective and efficient management. Dr. Drs. M. Hatta Bukittinggi Brain Hospital, a vertical technical implementing unit under the Ministry of Health, serves as the focus of this study, which aims to analyze the implementation of digital personnel administration services within the hospital. Employing a descriptive qualitative research method, data were collected through in-depth interviews, observations, and documentation. The study utilizes the Input-Process-Output (IPO) system approach. Findings indicate that: (1) the digitalization implementation aligns with existing policies; (2) while the majority of human resources comprehend the application, some lack understanding, hindering administrative processes; (3) the available infrastructure supports digitalization adequately, though certain areas require enhancements; (4) the implementation process functions effectively despite occasional issues such as server errors; and (5) the digitalization initiative significantly benefits personnel administration services, rendering them highly effective and efficient.